The mediating role of resilience between executive function and non-suicidal self-injury in Indonesian adolescents - Khairunnisa, Rania; Hendrawan, Donny (Humanitas: Indonesian Psychological Journal, 2025)
Adolescence is characterized by significant biological, psychological, and social changes, that bring challenges that may lead to maladaptive behaviors, such as non-suicidal self-injury (NSSI). Executive function and resilience are the factors that can affect NSSI behavior by promoting adaptive responses to challenges. Executive function supports emotional regulation and problem-solving, while resilience helps adolescents cope with stress. This study aims to explore how resilience mediates the relationship between executive function and NSSI. The Teenage Executive Function Inventory, Cognitive Flexibility Scale, Child and Youth Resilience Measure-Revised, and Deliberate Self-Harm Inventory were used in this study. Two hundred and eleven adolescents participated, consisting of 104 males and 107 females (SD = 0.501), aged 12-18 years (SD = 1.424). Data analysis was conducted using Hayes Macro Process Mediation Analysis. Results indicate resilience partially mediates the relationship between overall executive function and NSSI. However, resilience fully mediates the relationship between executive function dimensions separately—working memory, inhibitory control, and cognitive flexibility—and NSSI. These findings underscore the importance of resilience and executive function in understanding NSSI behavior among adolescents. Moreover, resilience and executive function can be considered by practitioners and parents as key targets for interventions aimed at preventing and reducing the prevalence of NSSI.